2017
DOI: 10.5387/fms.2016-16
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of non-invasive chronic fungal rhinosinusitis by cone beam CT: comparison with multidetector CT findings

Abstract: Objective : To investigate the accuracy of cone beam CT (CBCT) to diagnose non -invasive chronic fungal rhinosinusitis. Methods : Preoperative CT evaluation of non -invasive chronic fungal rhinosinusitis was performed by CBCT (3D Accuitomo 170 ® ) and traditional multidetector CT (MDCT) (Aquilion 32 ® ) in 13 and 38 patients with non -invasive chronic fungal maxillary sinusitis, respectively, in different facilities. Detection of intrasinus calcification was compared between these two groups. Results : Detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…Similar to standard multidetector CT, CBCT can confirm the diagnosis of CRS and identify anatomic variants for presurgical planning. One study showed decreased detection of intrasinus calcifications in patients with noninvasive fungal sinusitis compared with multidetector CT, although comparison between the 2 modalities was done in separate patient cohorts [34]. CBCT is limited in the evaluation of soft-tissue structures and therefore is not the imaging modality of choice if extrasinus disease is suspected [19,25].…”
Section: Spect or Spect/ct Paranasal Sinusesmentioning
confidence: 99%
“…Similar to standard multidetector CT, CBCT can confirm the diagnosis of CRS and identify anatomic variants for presurgical planning. One study showed decreased detection of intrasinus calcifications in patients with noninvasive fungal sinusitis compared with multidetector CT, although comparison between the 2 modalities was done in separate patient cohorts [34]. CBCT is limited in the evaluation of soft-tissue structures and therefore is not the imaging modality of choice if extrasinus disease is suspected [19,25].…”
Section: Spect or Spect/ct Paranasal Sinusesmentioning
confidence: 99%
“…Важлива роль в діагностиці хронічного запального процесу в синусі належить променевим методам дослідження, а саме -комп'ютерній томографії. До ознак грибкової природи синуситу належить наявність затемнення в просвіті синусу з характерними включеннями часток підвищеної променевої щільності, які можуть розміщуватись як дифузно -"зоряне небо", так і компактно [1,10].…”
unclassified
“…Існують різні пояснення щодо походження ділянок з підвищеною променевою щільністю в товщі грибкового тіла: частинки ретгенконтрастного пломбувального матеріалу; частинки грибкового тіла з високим вмістом цинку, як наслідок адсорбції з ферментів групи металопротеїназ [8]; та осифікати з вмістом кальцію [10,11].…”
unclassified